Wisdom-Oriented Counseling Approach Sebagai Alternatif Solusi Persoalan-Persoalan Kekerasan Anak dan Remaja Reorientasi Kepribadian (Prosiding Konseling Kearifan Nusantara (KKN), 2024)
The counselor's expertise in navigating the client's development from negative conditions to positive conditions does not only lie in their mastery of counseling theory. One thing that is thought to have a strong influence is the basic attitude of the counselor who cares about the benefit of the counselee (wisdom-oriented). There are a number of cognitive, emotive and conative characteristics, as well as strong character and behavior that counselors must have. Likewise, when helping clients whose needs are not being met, their goals are not being achieved, and especially those who are still young and are in the process of developing their self-identity, a counselor's caring attitude is needed. It is suspected that most of the perpetrators of acts of violence, including sexual violence, and intolerant attitudes occurred because they lost an environment full of love and hope. Is there anything the counselor can prepare for himself who cares about his welfare? Do you need an older counselor for that? How can the wisdom-oriented counseling approach be applied to help teenagers who are lazy?